PENGARUH DIMENSI KUALITAS JASA TERHADAP KEPUASAN KONSUMEN PADA PT POS INDONESIA CABANG MEDAN - Purba, Lesny (UNIKA Santo Thomas, 2012)
The research objective was to determine the influence of the dimensions of service quality on customer satisfaction. Populations are all consumers who use the mail service, PT Pos Indonesia Medan Branch in 2007. Study sample as many as 96 people. Data collection techniques used were questionnaires. Technique analysis is the chi square test. Of the research and discussion it can be concluded that the majority of respondents said they were satisfied (48%) for quality of service no significant relationship between the dimensions of service quality on customer satisfaction with PT Pos Indonesia Medan Branch. Advice given to the head of PT Pos Indonesia Medan Branch is to maintain the condition of the post office building, ease and clarity of the administration and courtesy of employees in serving customers. To improve customer satisfaction, the company should deliver the goods and mail to its destination on time, keeping consumer goods shipped by Berta handle consumer complaints, seriously.